USING OUTSIDE-CURRICULAR LEARNING SOURCES TO DEVELOP STUDENTS' SPEAKING SKILLS - Rajabova Zarafshon Davronovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. This article analyzes modern approaches to the development of speech skills in students, in particular, ways to increase the effectiveness of language learning through extracurricular educational resources. The author highlights the possibilities of forming students' oral and written speech based on extracurricular materials (works of art, audio-video resources, blogs and social networks).